2023
DOI: 10.1371/journal.pone.0277279
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial etiology of urinary tract infections in patients treated at Kenyan health facilities and their resistance towards commonly used antibiotics

Abstract: Background Evidence-based empirical antibiotic prescribing requires knowledge of local antimicrobial resistance patterns. The spectrum of pathogens and their susceptibility strongly influences guidelines for empirical therapies for urinary tract infections (UTI) management. Objective This study aimed to determine the prevalence of UTI causative bacteria and their corresponding antibiotic resistance profiles in three counties of Kenya. Such data could be used to determine the optimal empirical therapy. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…On the basis of the latter and other considerations; existence of ESBL, XDR)/or PDR pathogens in this setting cannot be overruled. Overall, our data align with multiple reports from the region [36,20,19]. In the past, experts have argued that a MAR >-2 originates from an ecological environment characterized by uncontrolled use of broad spectrum antibiotics [37].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…On the basis of the latter and other considerations; existence of ESBL, XDR)/or PDR pathogens in this setting cannot be overruled. Overall, our data align with multiple reports from the region [36,20,19]. In the past, experts have argued that a MAR >-2 originates from an ecological environment characterized by uncontrolled use of broad spectrum antibiotics [37].…”
Section: Discussionsupporting
confidence: 90%
“…The median age (mainly females) in Namibia was 28 and 32 years [18]. Similar pro les in other countries were as follows: Kenya 30.7 (±12.1) years and 81.5% women [19]; and Ghana: 30 (±28) years and 66.1% females [20]. The skew toward elderly male patients highlights differences in clinical practice in settings across SSA.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Previous similar studies have also reported a link between bacterial infections in urine and factors such as residing in rural areas, being uncircumcised, and experiencing frequent urination, which could be more prevalent in older age groups. Additionally, the frequency of resistance in urinary tract infections is higher due to patients often receiving prescribed antibiotics and self-administering them without supervision, particularly in regions where self-medication practices are common [ 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%